Viability of distribution system for dose of drugs in the neonatal Intensive Care Unit of a university hospital: a study based on a value (Research, Society and Development, 2022)
Medication access is considered a fundamental human right but must be rationally dispensed. This study aimed to compare the direct costs of the mixed drug dispensing system used in a neonatal intensive care unit, with a simulation of drug distribution system for unit through a hospital pharmacotecnical standardized at resolution-RDC 07/2007 by Brazilian Ministry of Health. It is a cross-sectional retrospective, and analytical study, with a qualitative and quantitative approach. The variables were obtained through the analysis of prescription and dispensing reports, over a one year, related to pharmacological therapy, use and associated costs. The simple comparative analysis of the exclusive costs with medication consumption in the mixed dispensing model and in the simulated scenario showed a savings of 27.07% that means R $27, 072, 66, to the last one. The injectable drugs group contributed mostly to this savings, approximately 95.0%, that means R$25,719.97. Although that result showed less significant economic contributions for oral medications, they might possibly show positive effects for patient safety, arising from reduction of errors of drugs administration routes, risks of microbiological contamination and work overload, not measured here. In addition, the integration of the pharmacist into the multidisciplinary team. However, more complex economic evaluations, which allow the measurement of these and other beneficial effects, are necessary to support managers and specialists into decision-making process.